The light between oceans eaudiobook - Stedman, M.L (Recorded Books, Inc., 2014)
In her mesmerizing first novel The Light Between Oceans, M.L. Stedman examines how human longing can lead to heartbreak. In the early 1900s, on a small island off the coast of Australia, lighthouse keeper Tom Sherbourne and his wife Isabel live a quiet, isolated life- until a boat carrying a dead man and an infant washes ashore. Childless, Isabel is determined to keep the baby as her own, so they don' t report the incident. But when Tom and Isabel return to the mainland two years later, dire consequences await.